Treatment of an ostial and a bifurcation lesion with a new directional atherectomy device. Issue 8 (14th July 2004) - Favero, L; Simpson, J B; Reimers, B
Abstract : Two cases of directional coronary atherectomy performed with a new 8 French monorail device for selective plaque excision are illustrated. This report underlines the technical characteristics of this new device, which allows the negotiation of complex coronary anatomy and emphasises the potential utility of directional coronary atherectomy in bifurcation and ostial lesions.